Legal Protection for Child Criminals at the Juvenile Detention Center: Study of Psychiatric Health - Arief Budiono (Journal of Global Pharma Technology, 2020)
Children are the young buds of the human beings. They are created by Allah as the best creature. But, they may be placed at a low degree as a human being if they are not obedient to Allah by doing evil things. To maintain their degree as a human being as intended by Allah in the creation of human beings, which is as the leaders of earth and as beloved servants, the human beings are obligated to have faith in Allah and carry out good deeds. But, not every person can grow and develop normally. Some cannot do so as they carried out criminal actions and have their liberties and their childhood taken away. This research is focused on the legal protection for criminal children at the Juvenile Detention Center through the legal-health analysis. The data obtained are then analyzed using the Capacities and Vulnerabilities Analysis (CVA).